Review of Martha Feldman. 2007. Opera and Sovereignty: Transforming Myths in Eighteenth-Century Italy. Chicago and London: University of Chicago Press - Burgess, Geoffrey (Current Musicology, 2008)
Feldman’s most recent publication admirably demonstrates the thoroughness and insightfulness of her work. To her masterful study of opera seria she brings not only her own encyclopedic knowledge, laborious archival work, astute evaluation of disparate materials, and imaginative presentation, but also a critical appreciation of a vast array of related scholarship. In Opera and Sovereignty she revisits topics already presented in article form, most notably in “Magic Mirrors,” which appeared in a special issue of JAMS dedicated to the dialogue between anthropology and musicology and which prepared much of the methodological ground of her later work. Opera and Sovereignty is a book of astounding breadth of subject matter, rich source materials, and provocative methodologies. It traces opera seria’s history from the apogee of Metastasian influence and the triumphant celebration in royalist houses like the Teatro San Carlo in Naples.